COVID 19 second wave - What has changed since the first wave - Madiha Abdul Nazer; Latha Ragunathan; P Bharathi; I Deepika (Wolters Kluwer Medknow Publications, 2022)
A pandemic named SARS-COV2 COVID 19 affected many people's life in different ways globally. The normal life is still far away, lockdown rules have been relaxed in many countries. Morbidity and mortality increased a lot after the first wave. COVID-19 has affected medical education in a significant way. Most of the patients were asymptomatic during the second wave and some had symptoms such as myalgia, fever, and cough, which complicated to pneumonia, respiratory distress, and thromboembolic complications. There have been the development of many vaccines such as Covaxin, Pfizer-BioNTech, Covishield, Sputnik V, and Moderna, and these vaccinations have been given to frontline medical workers, people with comorbidities, aged people, etc., with high priority and then the general population. Many pregnant and peripartum women were put on Extracorporeal Membrane Oxygenation (ECMO) in severe to critical cases. A new black fungus was found in post-COVID 19 infections. It was named mucormycosis which usually affected immunocompromised people. There is a high importance in the examination of all the different epidemiological variables of all the places in all the regions across the world, to understand the mutations, and severity of the disease and also to be prepared. Many studies done on COVID-19 in first and the second wave was reviewed in detail and were compared for this review.